Effectiveness of a service design training program to improve clinical nurses' compassion and problem-solving in Korea. - Keum-Seong Jang; Mikyoung Lee; Hyunyoung Park; Kyung-Hee Chung; Myeong Baek; Young-Ran Kweon; Yun-Hee Kim (PLoS ONE, 2022)
Service design is an innovative tool used to improve the quality of patient experience, therefore, making it necessary for nurses to be able to implement it. The aim of this study was to examine the effects of a training program for patient experience-based nursing service design (PEN-SD) on clinical nurses' compassion and problem-solving ability. This study employed a mixed-methods design: a one-group, pretest-posttest design was used as the quantitative approach, and structured interviews were used as the qualitative approach. The participants were 21 nurses recruited from a university hospital in Korea. A PEN-SD training program was conducted from September 1 to October 6, 2018. After the training program, the participants' compassion significantly improved (p = .025) but there was no significant difference in their problem-solving ability (p = .313). In the structured interviews, majority of the participants (n = 17) felt that they were able to consider problems from the patient's perspective. They also reported being able to identify solutions to problems through careful observation (n = 5). The PEN-SD training program was effective in improving compassion among nurses.